Pattern-Type Separation of Triacylglycerols by Silver Thiolate×Non-Aqueous Reversed Phase Comprehensive Liquid Chromatography - Paola Arena; Danilo Sciarrone; Paola Dugo; Paola Donato; Luigi Mondello (Separations, 2021)
Triacylglycerols (TAGs), as the main components of edible oils and animal fats, are responsible for the nutritional value, organoleptic features and technological properties of foods; each lipid matrix shows a unique TAG profile which can serve as fingerprint to ensure the quality and authenticity of food products. The high complexity of many foodstuffs often makes untargeted elucidation of TAG components a challenging task; thus, more efficient separation techniques may be mandatory. In this research, the TAG profile of a borage (Borago officinalis) seed oil was obtained by two-dimensional comprehensive liquid chromatography (LC×LC), by the coupling of silver thiolate and octadecylsilica monodisperse materials. A total 94 TAG compounds were identified by ion trap-time of flight detection, using atmospheric pressure ionization, with the degree of unsaturation varying from 0 to 9, and partition values ranging from 36 to 56. The group-type separation afforded by this analytical approach may be useful to quickly fingerprint TAG components of oil samples.